Effect of extreme climatic events resulting in prolonged precipitation on the reproductive output of sea turtles - Rivas, M. L. (2018)
Anthropogenic climate change is predicted to increase the variation in storm patterns in some areas in the coming decades. This variation in mean rainfall and increase in mean temperature could increase the extinction risk of species with temperature dependent sex determination. Taking into account that sea turtle reproductive output depends on climatic conditions, such as precipitation and temperature, extreme climatic events could affect the mortality of eggs and hatchlings. Our main goal was to assess the effects of extreme climatic events resulting in prolonged precipitation episodes on the reproductive output of leatherback turtles Dermochelys coriacea and how these events might reduce hatchling production. To study how short periods of protracted rainfall affect leatherback turtle reproductive output, we recorded (1) the hatching success of n = 48 nests located at 50, 75 and 90 cm depths under sun and shaded treatments from 2013 to 2015 at the Pacuare Reserve in Caribbean coast of Costa Rica, (2) the water table level and (3) sand moisture at 10, 25, 50, 75 and 100 cm depths. In addition, we assessed changes in seasonal precipitation, nest abundance and the annual hatching success of leatherbacks over time. The results show that prolonged precipitation significantly influenced hatching success. Protracted rainfall increased the water table levels and sand moisture in some places, which consequently increased egg mortality in deeper nests. These effects may be higher considering the expected increase in storm frequency. Thus, the assessment of the effects of these extreme events on nesting grounds is necessary to predict the potential extinction risk of sea turtle populations.